Label-free metabolic imaging by mid-infrared optoacoustic microscopy in living cells - Pleitez, Miguel A.; Khan, Asrar Ali; Solda, Alice; Chmyrov, Andriy; Reber, Josefine; Gasparin, Francesca; Seeger, Markus R.; Schaetz, Benedikt; Herzig, Stephan; Scheideler, Marcel; Ntziachristos, Vasilis (Nature Biotechnology, 2020)
We develop mid-infrared optoacoustic microscopy (MiROM) for label-free, bond-selective, live-cell metabolic imaging, enabling spatiotemporal monitoring of carbohydrates, lipids and proteins in cells and tissues. Using acoustic detection of optical absorption, MiROM converts mid-infrared sensing into a positive-contrast imaging modality with negligible photodamage and high sensitivity. We use MiROM to observe changes in intrinsic carbohydrate distribution from a diffusive spatial pattern to tight co-localization with lipid droplets during adipogenesis.
CRIS-Team Scopus Importer:2023-03-08